Ship anemometer bias management - Thornhill, Eric; Wall, Alanna; McTavish, Sean; Lee, Richard (Ocean engineering, 2020)
Wind measurements made on ships are used for general navigation, maritime operations, and in some cases logged to support oceanographic research. They are particularly important for aircraft-carrying ships as operations can be restricted in certain wind conditions. Shipboard wind measurements are subject to biases and inaccuracies as a result of air flow changing as it passes over and around the ship, its structures, and features. Ship-induced wind distortion and the resulting bias on anemometer readings can range from insignificant to severe. Anemometer bias cannot be completely eliminated for all conditions, but it can be managed so that reliable and accurate assessments of wind at sea can be identified. This paper describes the basic concepts related to ship wind distortion along with procedures and considerations on how bias can be quantified using simulations or model tests and validated using sea trials. An example case of a helicopter-carrying frigate is used to demonstrate the process of quantifying bias, calculating metrics, determining useful ranges, and developing and applying correction-functions. Wind tunnel measurements and a sea trial successfully demonstrated and validated the proposed ship anemometer bias management methodology. •Wind flow is distorted as it moves over and around a ship and its structures.•Shipboard measurement of wind is biased by ship-induced flow distortion.•Accurate wind measurements are particularly important for aircraft-carrying ships.•Ships may require multiple anemometers to ensure accurate wind measurement for all wind angles.•In some cases, algorithms can be developed to correct for bias using data from simulations or model tests.